PERANAN WANITA NELAYAN DALAM MENINGKATKAN PENDAPATAN RUMAH TANGGA DI KELURAHAN AMPENAN SELATAN KECAMATAN AMPENAN KOTA MATARAM - IDA AYU KETUT MARINI; IDA BAGUS EKA ARTIKA (Universitas Mahasaraswati K. Mataram, 2023)
This study aims to determine the role of fisherwomen in improving the economy of fisherman households in Ampenan Selatan Village, Ampenen District, Mataram City. The researcher used a purposive sampling technique in determining the sampling, namely the sampling technique with certain considerations, totaling 52 fisherman households. To analyze the problem formulation of the role of fisherwomen in improving the economy of fisherman households, researchers used the Chai-square test statistical analysis tool. The results showed that 31 female fishermen had jobs as laborers, 10 female fishermen as traders, 5 female fishermen as housewives, 5 female fishermen as household helpers and as many as 1 female fisherman as breeders. The role of fisherwomen in improving the fishermen's household economy is carried out by comparing the frequency distribution of observations or observations with the expectation distribution using Chai-Sqauare (X2) the result is 28.085, so H0 is rejected which means that there is a role for fisherwomen in improving the household economy fishermen (HI received).